A patent review of arginine methyltransferase inhibitors (2010–2018). (1st February 2019) - Li, Xiao; Wang, Chen; Jiang, Hao; Luo, Cheng
ABSTRACT: Introduction : Protein arginine methyltransferases (PRMTs) are fundamental enzymes that specifically modify the arginine residues of versatile substrates in cells. The aberrant expression and abnormal enzymatic activity of PRMTs are associated with many human diseases, especially cancer. PRMTs are emerging as promising drug targets in both academia and industry. Areas covered : This review summarizes the updated patented inhibitors targeting PRMTs from 2010 to 2018. The authors illustrate the chemical structures, molecular mechanism of action, pharmacological activities as well as the potential clinical application including combination therapy and biomarker-guided therapy. PRMT inhibitors in clinical trials are also highlighted. The authors provide a future perspective for further development of potent and selective PRMT inhibitors. Expert opinion : Although a number of small molecule inhibitors of PRMTs with sufficient potency have been developed, the selectivity of most PRMT inhibitors remains to be improved. Hence, novel approaches such as allosteric regulation need to be further studied to identify PRMT inhibitors. So far, three PRMT inhibitors have entered clinical trials, including PRMT5 inhibitor GSK3326595 and JNJ-64619178 as well as PRMT1 inhibitor GSK3368715. PRMT inhibitors with novel mechanism of action and good drug-like properties may shed new light on drug research and development progress.